The Role of International Covenant on Economic, Social and Cultural Rights in the Protection of Small and Medium Enterprises in Yogyakarta Towards the ASEAN Economic Community 2015 - Yovi Cajapa Endyka (FH IH 16 UMY 045, 2016)
The ASEAN Economic Community (AEC) is one of the pillars of the ASEAN Community that were set out in the Bali Concord II. AEC shall be the goal of regional economic integration by 2015. AEC envisages the following key characteristics: (a) a single market and production base, (b) a highly competitive economic region, (c) a region of equitable economic development, and (d) a region fully integrated into the global economy. Yogyakarta is a city in Indonesia where many citizens are involved in the business, actually in small and medium enterprises (SMEs). Based on the data obtained from the Department of Trade, Industry and Cooperatives Yogyakarta, in 2015 there were 230.047 SMEs industries. With the increasingly fierce competition as a result of the single market of the AEC will very likely have an impact on the survival of these SMEs, since many imported-products will flood the domestic market. Indonesia has ratified International Covenant on Economic, Social and Cultural Rights (ICESCR). On October 28, 2005, the Indonesian government ratifies the ICESCR into ICESCR Ratification Act 2005. This study aims to analyze the protection of small and medium enterprises in Yogyakarta towards ASEAN Economic Community based on economic, social and cultural rights. The study is normative legal research which was conducted through library research. The results shows the government has a binding obligation to take various measures and policies to implement the obligation such as â€œto respectâ€, â€œto protectâ€ and â€œto fulfilâ€ human rights toward SMEs in Yogyakarta, especially in Economic, Social and Cultural Rights. Keywords: The ASEAN Economic Community (AEC) is one of the pillars of the ASEAN Community that were set out in the Bali Concord II. AEC shall be the goal of regional economic integration by 2015. AEC envisages the following key characteristics: (a) a single market and production base, (b) a highly competitive economic region, (c) a region of equitable economic development, and (d) a region fully integrated into the global economy. Yogyakarta is a city in Indonesia where many citizens are involved in the business, actually in small and medium enterprises (SMEs). Based on the data obtained from the Department of Trade, Industry and Cooperatives Yogyakarta, in 2015 there were 230.047 SMEs industries. With the increasingly fierce competition as a result of the single market of the AEC will very likely have an impact on the survival of these SMEs, since many imported-products will flood the domestic market. Indonesia has ratified International Covenant on Economic, Social and Cultural Rights (ICESCR). On October 28, 2005, the Indonesian government ratifies the ICESCR into ICESCR Ratification Act 2005. This study aims to analyze the protection of small and medium enterprises in Yogyakarta towards ASEAN Economic Community based on economic, social and cultural rights. The study is normative legal research which was conducted through library research. The results shows the government has a binding obligation to take various measures and policies to implement the obligation such as â€œto respectâ€, â€œto protectâ€ and â€œto fulfilâ€ human rights toward SMEs in Yogyakarta, especially in Economic, Social and Cultural Rights. Keywords: ICESCR, AEC 2015, SMEs, Yogyakarta, Economic, Social and Cultural Rights..